PENGARUH PENERAPAN TOTAL QUALITY MANAGEMENT TERHADAP KEPUASAN KERJA KARYAWAN - Ade Muhammad Zikril Hakim; Samsir Samsir; Anggia Paramitha (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to determine the effect of applying Total Quality Management application on PT. Tirta Guna Abadi Padang of employees Job Satisfaction. The population in this study includes all employees at PT. Tirta Guna Abadi Padang, totaling 31 people. Primary data was collected by questionnaire as an instrument to prove the result of the research. to the hypothesis in this study is tested using multiple regression analysis with the help of SPSS (Statistical Prorgam For Social Sciences). The sampling technique is a census method (31 employees at PT Tirta Guna Abadi Padang). The results showed that: 1) there is a positive and significant effect of recognition and appreciation of employee work satisfaction PT. Tirta Guna Abadi Padang, 2) there is a positive and significant influence of teamwork on employee work satisfaction of PT. Tirta Guna Abadi Padang, 3) there is a positive and significant influence of organizational culture on employee work satisfaction of PT. Tirta Guna Abadi Padang.Keywords : Recognition and Awards, Teamwork, Organizational Culture, Employee Satisfaction